2017
DOI: 10.1021/acs.analchem.7b04134
|View full text |Cite
|
Sign up to set email alerts
|

An Interface Equilibria-Triggered Time-Dependent Diffusion Model of the Boundary Potential and Its Application for the Numerical Simulation of the Ion-Selective Electrode Response in Real Systems

Abstract: A simple dynamic model of the phase boundary potential of ion-selective electrodes is presented. The model is based on the calculations of the concentration profiles of the components in membrane and sample solution phases by means of the finite difference method. The fundamental idea behind the discussed model is that the concentration gradients in both membrane and sample solution phases determine only the diffusion of the components inside the corresponding phases but not the transfer across the interface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…7-9) [7]. The equations which have been used to describe the interface have been criticized [14], and possible modifications were recommended [15][16][17]. Here we describe the responses of a SC-ISE with the presence of a water layer between the ion-selective membrane and the solid-contact to the concentration changes used in the water layer test.…”
Section: Resultsmentioning
confidence: 99%
“…7-9) [7]. The equations which have been used to describe the interface have been criticized [14], and possible modifications were recommended [15][16][17]. Here we describe the responses of a SC-ISE with the presence of a water layer between the ion-selective membrane and the solid-contact to the concentration changes used in the water layer test.…”
Section: Resultsmentioning
confidence: 99%
“…The obvious advantage of this material is its hydrophobicity, large capacitance and good solubility in the membrane matrix. [47][48][49] It was found that in some cases the earlier model shows principal limitations that may lead to failure of the calculations. 47 The authors studied the influence of the boundary conditions and simulation parameters to find a solution for this problem.…”
Section: Solid-contact Based On Other Materialsmentioning
confidence: 99%
“…This group proposed to modify the established calculation protocol and termed it an interface equilibria-triggered time-dependent diffusion model. 49 52 It included Nikolsky-Eisenman equation and its permutated form, the most rigorous self-consistent model, which is however mathematically complex, and two different approximations valid for cases of low level of interference. One of these approximations was introduced for the first time.…”
Section: Solid-contact Based On Other Materialsmentioning
confidence: 99%
“…The calculations were carried out for "pure" solutions of the corresponding amine in the absence of foreign ions. The diffusion of components inside the corresponding phases was calculated using equations identical to those presented in the original model [12].…”
Section: Electrodes For Determination Of Lipophilic Ammonium Cationsmentioning
confidence: 99%
“…A simple and, in our opinion, universal solution to this problem was proposed in the framework of the interface equilibria‐triggered (IET) dynamic diffusion model, according to which each calculation cycle for an instant of time t begins with recalculation of equilibrium concentrations of each component in rather thin near‐boundary layers. To perform this recalculation, the concentrations of the corresponding components in near‐boundary layers attained at the previous instant of time t–δt as the result of diffusion are used and interphase and intra‐phase equilibrium constants together with material balance and electroneutrality conditions in these layers are taken into account . The obtained corrected values of concentrations are then used to recalculate the concentrations of each component in all other elementary layers of the membrane and in the aqueous diffusion layer (from the first layer to the last one) taking into account diffusion processes.…”
Section: Introductionmentioning
confidence: 99%